On bootstrapping regression model with random resample size - Nguyễn Hồng Nhung (Journal of Technical Education Science, 2017)
To find confidence interval for regression coefficients, classical methods require the distribution of errors. Under mild conditions, without knowing the distribution of errors, the bootstrap approximation with fixed or random resample sizeto estimate the distribution of the least squares is valid. In this paper, the author presents algorithms to determine regression coefficients of the bootstrap regression model with random resample size Nn.Nn is a positive integer-valued in m, n with the ability to be the same at all values, where m is the smallest positive integer greater than or equal to n/4. Matlab software is used to seek the empirical bootstrap regression coefficients and create analysis comments.